SPORT, NATURE AND ETHICAL CONSCIENCE: ABOUT THE ROLE OF MIMESIS IN THE EDUCATIONAL PHILOSOPHY OF ERASMUS OF ROTTERDAM (Fiep Bulletin - online, 2014)
The objective of this paper consists on an investigation about the arguments of the Renaissance thinker Erasmus de Rotterdam in favor of the thesis that the imitation of animal behavior represents a secure pedagogical strategy for the improvement or corroboration of people moral trends considering how they actually behave in sports practices. For this purpose, the arguments of the author displayed between the 34th and 39th sessions on the classic book De Pueris were commented, accounting Renaissance as a philosophical movement. Then, based on this understanding, one defined the formal positions assumed by sport in the thought of Erasmus.
Keywords: Sport; Mimesis; Moral Education; Nature; Erasmus of Rotterdam